Sosialisasi Pembangunan Ekonomi Desa Terpadu Desa Talang Kemang Kecamatan Semidang Alas Maras Kabupaten Seluma - Azuwandri, Azuwandri; Hafiz , Muhammad; Arlita, Arlita (Universitas Dehasen Bengkulu, 2021)
Socialization of Integrated Village Economic Development is a strategic effort to improve the welfare of the people of Talang Kemang Village, Semidang Alas Maras District, Seluma Regency. This study aims to assess the impact and effectiveness of socialization in strengthening community participation in integrated village economic development. The research method used was a survey and interviews with various related parties, such as farmers, breeders, small business actors, as well as representatives of the village and sub-district governments.The results show that socialization plays an important role in improving community understanding of the concept and benefits of integrated village economic development. Community participation in local economic activities increased significantly after the socialization. In addition, cooperation between the government, the community, and the private sector also improved in supporting the implementation of integrated village economic development programs.However, the research also identified several obstacles faced in the socialization process, such as the lack of access to information and the lack of active involvement of some community groups. Therefore, it is recommended that the socialization program be further strengthened through various inclusive and participatory communication methods, and involve more related parties to ensure the success of integrated village economic development in Talang Kemang Village.In conclusion, the socialization of integrated village economic development in Talang Kemang Village made a positive contribution in increasing community understanding and participation in efforts to improve local economic welfare. However, further efforts are still needed to overcome the various obstacles faced so that this program can run more effectively and sustainably.